OSS Operation Black Mail one woman's covert war against the Imperial Japanese Army - Todd, Ann (Naval Institute Press, 2017)
"OSS Operation Black Mail is the story of a remarkable woman who fought World War II on the front lines of psychological warfare. Elizabeth P. McIntosh spent eighteen life-changing months serving in the Office of Strategic Services in what has been called the "forgotten theater," China-Burma-India, where she met and worked with people as diverse as Allen Dulles, Julia Child, and Ho Chi Minh. Her craft was black propaganda, and her mission was to demoralize the enemy through prevarication and deceit, and ultimately, convince him to surrender. Betty's effectiveness stemmed from her ability to target not merely the Japanese soldier but the man within: the husband, the son, the father. Her black propaganda was boldly experimental and ground-breaking, destined to play a key role in the Cold War"...
Includes bibliographical references and index
Keywords: McIntosh, Elizabeth P. -- 1915-2015; United States -- Office of Strategic Services -- Biography; USA -- Office of Strategic Services; Geschichte 1944-1945; Psychologie; Weltkrieg (1939-1945); Women spies -- United States -- Biography; World War, 1939-1945 -- Secret service -- United States; World War, 1939-1945 -- Campaigns -- Asia; World War, 1939-1945 -- Psychological aspects; Zweiter Weltkrieg; Psychologische Kriegführung; Asien; USA; China; Biografie